Recent progress of electrochemical reduction of CO₂ by single atom catalysts - Wang, Tian (2023)
Powered by electricity from renewable energies, electrochemical reduction of CO2 could not only efficiently alleviate the excess emission of CO2, but also produce many kinds of valuable chemical feedstocks. Among various catalysts, single atom catalysts (SACs) have attracted much attention due to their high atom utilization efficiency and expressive catalytic performances. Additionally, SACs serve as an ideal platform for the investigation of complex reaction pathways and mechanisms thanks to their explicit active sites. In this review, the possible reaction pathways for the generation of various products (mainly C1 products for SACs) were firstly summarized. Then, recent progress of SACs for electrochemical reduction of CO2 was discussed in aspect of different central metal sites. As the most popular and efficient coordination modulation strategy, introducing heteroatom was then reviewed. Moreover, as an extension of SACs, the development of dual atom catalysts was also briefly discussed. At last, some issues and challenges regarding the SACs for CO2 reduction reaction (CO2RR) were listed, followed by corresponding suggestions.